Pendidikan Keterampilan Kerja Bagi Warga Berkebutuhan Khusus Melalui Pelayanan Keliling di Pedesaan - Haryanto -- (Jurnal Pendidikan dan Kebudayaan, 2010)
This study aimed to investigate the intensity and effectiveness, the relationship between th intensity of a model service and skills, the effectiveness of the model service, and the effect of the model on people with special needs in terms of the work accuracy level with accurate products, work time accuracy, and work perfection with good results. This study was a research and development study. The research subjects were people with special needs in the productive age who have not held permanent jobs. The study was conducted in the area of Gunungkidul in the period of 2008-2009. The data were collected through observations, interviews, demonstrations, and tests. The data were analyzed by means of the mixed methods involving the quantitative and qualitative approaches. The quantitative data were analyzed by LISREL and the qualitative data by the interactive model. The result showed that the subject’s skill may changed tin a positive direction in accordance with intensity, the attitude change among people with special needs occur throgh optimal work, beside building intensity also need to remain the work accuracy and the time puretually, the impact of the model result for the people with special needs not only about having the work skill but phsycologically they felt noted, respected, and it raises their life spirit, to work and live independently. ABSTRAKPenelitian ini bertujuan untuk mengetahui intensitas, efektivitas, hubungan antar intensitas pelayanan model dengan keterampilan, dan dampak model bagi warga berkebutuhan khusus. Subjek penelitian warga berkebutuhan khusus usia produktif. Lokasi penelitian di wilayah Gunungkidul, jenis penelitian Research and Development, dilaksanakan tahun 2008-2009. Teknik pengumpulan data menggunakan observasi, intervu, demonstrasi, dan tes. Analisis data menggunakan pendekatan kuantitatif dan kualitatif. Data kuantitatif diolah dengan program LISREL, data kualitatif dianalisis melalui model interaktif. Hasi penelitian menunjukkan bahwa keterampilan subjek dapat berubah dengan arah positif sesuai dengan berubahnya intensitas, terdapat perubahan perilaku warga berkebutuhan khusus melalui partisipasi masyarakat, didukung sarana dan prasarana yang memadai, untuk menjaga keterampilan kerja yang optimal, selain membangun intensitas juga perlu dijaga keakuratan kerja dan ketepatan waktu, dampak hasil model bagi warga berkebutuhan khusus tidak sekedar memiliki keterampilan kerja tetapi secara psikologis mereka merasa diperhatikan, dihargai, hal ini menumbuhkan semangat hidup berkarya, dan hidup mandiri.